Health risk perception and exercise intention of college students: a moderated mediation model of health anxiety and lay theories of health - Wang, Kun; Liu, Chen; Yang, Xiao; Wang, Yue (Frontiers in Psychology, 2024)
Background Health risk perception is an important predictor of health-protective behaviors according to the health belief model. However, the underlying mechanism connecting health risk perception and exercise behaviors is not well understood. The current study investigates how health risk perception predicts college students' exercise intention in the post-pandemic era in China and analyzes the mediating effect of health anxiety and the moderating effect of lay theories of health. Materials and methods This cross-sectional study adopted convenience sampling and recruited 767 students from a province in central China. The Health Risk Perception Scale, Health Anxiety Scale, Lay Theories of Health Scale, and the Chinese version of the Exercise Intention Scale were used to measure the levels of health risk perception, health anxiety, implicit health theory, and exercise intention, respectively. Results The results of the moderated mediation model indicated that the health risk perception of college students significantly and positively affected exercise intention (β = 0.110, t = 2.852, p < 0.01). Meanwhile, the indirect effect of health anxiety on the relationship between health risk perception and exercise intention was significant. Furthermore, lay theories of health buffered the association between health anxiety and exercise intention, according to the moderated mediation analysis (β = 0.068, t = 2.067, p < 0.05). For college students holding incremental health theory, the influence of health anxiety on exercise intention was positively and statistically significant. Conclusion The health risk perception of college students can lead to health anxiety, which can positively affect their exercise intention. In addition, lay theories of health can moderate the effect of health anxiety on exercise intention. The results have practical implications for developing effective, applicable, and scalable interventions to promote physical exercise by reducing the level of entity theory of health or increasing the level of incremental theory.